Seasonal-Dial Shifts of Ichthyoplankton Assemblages and Plastic Debris around an Equatorial Atlantic Archipelago - Lima, André R. A.; Barletta, Mario; Costa, Monica F. (Frontiers in Environmental Science, 2016)
Seasonality was a stronger influence in the ichthyoplankton assemblages around the Saint Peter and Saint Paul Archipelago (SPSPA) than distance from the islands. Plastic debris were ubiquitous and although it presented diel trends, no other spatiotemporal patterns was showed. Larval Oxyporhamphus micropterus was the most important taxa (29.37% of the total catch), followed by Ceratoscopelus warmingii and Entomacrodus vomerianus. Exocoetidae eggs represented 41.01%. Mesopelagic fish larvae dominated the community. Myctophidae had the highest species richness (15). Four larval fish assemblages occured: (1) nighttime demersal/bathydemersal (Anguillidae, Congridae); (2) daytime mesopelagic/bathypelagic/epipelagic (Myctophidae, Cyclothone acclinidens); (3) daytime epipelagic (Exocoetidae, Coryphaena hippurus, Thunnus albacares) and (4) nighttime reef and demersal (Blennidae, Pomacentridae, Lutjanidae). The dry season (lower temperature, higher chlorophyll a and higher SW wind velocity) influenced the first two assemblages. The rainy season (higher temperatures and lower NW wind velocity) influenced the last two. Nighttime abundance of dominant species in the rainy season suggests diel vertical migration nearshore. Plastics were 2.12 times more abundant than the most abundant fish larvae. Comparable amounts of larvae and plastics in the water column increase the chances of interaction between these two compartments and might disturb the local marine food web and promote the transfer of microplastic from one habitat to another, especially when smaller taxa contaminated by ingested fragments are preyed by migratory animals such as marine birds and tuna. A study around the area concluded that at least a part of the plastic debris can have local source due to fishing activities. Small-scale oceanographic mechanisms such as the interaction between the topography and currents (SEC and EUC) seem to be responsible for the retention of fish eggs, fish larvae and plastics around SPSPA.